2023
DOI: 10.3390/fishes8030145
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis Identifies MAPK Signaling Pathway Associated with Regulating Ovarian Lipid Metabolism during Vitellogenesis in the Mud Crab, Scylla paramamosain

Abstract: The mud crab, Scylla paramamosain, has abundant nutrients in the ovary, where numerous lipids accumulate during ovarian maturation. However, the mechanism behind the accumulation of lipids in the ovary of mud crab during ovarian maturation is largely unknown. This study conducted a comparative transcriptome analysis of the ovaries of mud crabs at various stages of ovarian maturation. A total of 63.69 Gb of clean data was obtained, with a Q30 of 93.34%, and 81,893 unigenes were identified, including 10,996 diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
1
4
0
Order By: Relevance
“…The histology results were then interpreted. A previous study confirmed all mud crabs immediately after hatching were at the same starting point of the early vitellogenesis stage (stage III, ovarian color light-yellow) [53]. The ovarian stages in our study were distinguished as the early vitellogenesis stage (stage III, light-yellow) and the late vitellogenesis stage (stage IV, orange) [54,55], as confirmed by both morphology and histology.…”
Section: Tissue Collection and Histologysupporting
confidence: 89%
See 3 more Smart Citations
“…The histology results were then interpreted. A previous study confirmed all mud crabs immediately after hatching were at the same starting point of the early vitellogenesis stage (stage III, ovarian color light-yellow) [53]. The ovarian stages in our study were distinguished as the early vitellogenesis stage (stage III, light-yellow) and the late vitellogenesis stage (stage IV, orange) [54,55], as confirmed by both morphology and histology.…”
Section: Tissue Collection and Histologysupporting
confidence: 89%
“…A pea-sized piece of each tissue was transferred to Bonn fixation for about 24 h and then washed with 70% alcohol three times before putting it into 70% alcohol for −20 • C preservation. Paraffin slices were stained and dehydrated as previously described [53]. The histology results were then interpreted.…”
Section: Tissue Collection and Histologymentioning
confidence: 99%
See 2 more Smart Citations
“…The upregulation of lrp8 and lrp13 expression promoted intracellular yolk granule formation in stage IV oocytes [8]. Enhanced expression of genes in the MAPK signaling pathway was found to activate the PPAR signaling pathway via protein-protein interactions, thereby regulating lipid metabolism and facilitating oocyte development [9].…”
Section: Introductionmentioning
confidence: 99%